Residual risk reduction opportunities in patients with chronic coronary syndrome. Role of dual pathway inhibition. Issue 7 (2nd July 2020) - González-Juanatey, José R.; Almendro-Delia, Manuel; Cosín-Sales, Juan; Bellmunt-Montoya, Sergi; Gómez-Doblas, Juan José; Riambau, Vincent; García-Moll, Xavier; García-Alegría, Javier; Hernández, José Luis; Lozano, Francisco S.; Suarez Fernández, Carmen
ABSTRACT: Introduction: In this review, the role of the rivaroxaban-plus-aspirin approach (dual pathway inhibition – DPI) in patients with chronic coronary syndrome (CCS) and to perform practical recommendations about its use was updated. Areas covered: The contents of this review were proposed in an expert meeting. To identify relevant articles, a systematic search of Medline/Embase was performed (to July 2019), using the key words 'rivaroxaban', 'vascular dose', 'COMPASS' and 'coronary artery disease' in the search strategy. Expert opinion: Despite current antithrombotic strategies (single/dual antiplatelet therapy) have decreased rates of recurrent cardiovascular events among patients with CCS, residual risk remains unacceptably high. The COMPASS trial showed in CCS patients that compared with aspirin 100 mg rivaroxaban 2.5 mg bid plus aspirin 100 mg reduced the risk of major cardiac events, cardiovascular hospitalization and mortality, without an increase of intracranial or fatal bleedings. Importantly, residual risk with the rivaroxaban plus aspirin approach was lower than with different dual antiplatelet therapy regimens. The rivaroxaban plus aspirin strategy is of particular benefit in patients with CCS and high-risk cardiovascular feature (i.e. ≥2 vascular beds, heart failure, renal insufficiency, peripheral artery disease, previous stroke or diabetes) and should be considered in these populations.